2019
DOI: 10.1021/acs.joc.9b00248
|View full text |Cite
|
Sign up to set email alerts
|

Halo-1,2,3-triazolium Salts as Halogen Bond Donors for the Activation of Imines in Dihydropyridinone Synthesis

Abstract: In the past decade halogen bond (XB) catalysis has gained considerable attention. Halo-triazoles are known XB donors, yet few examples detail their use as catalysts. As a continuation of our previous work the catalytic properties of substituted enantiomerically pure halo-triazolium salts were explored in the reaction between an imine and Danishefsky’s diene leading to the formation of dihydropyridinone. The catalytic activity of the XB donors was highly dependent on the choice of the halogen atom and on the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
42
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 71 publications
1
42
0
Order By: Relevance
“…Previous publications clearly found that for the activation of neutral compounds, counter anions more weakly coordinating than triflate are necessary . Thus, an exchange to the corresponding BAr F 4 salt was performed via simple metathesis with TMABAr F 4 , affording 9 Im‐CF3‐BArF4 …”
Section: Resultsmentioning
confidence: 99%
“…Previous publications clearly found that for the activation of neutral compounds, counter anions more weakly coordinating than triflate are necessary . Thus, an exchange to the corresponding BAr F 4 salt was performed via simple metathesis with TMABAr F 4 , affording 9 Im‐CF3‐BArF4 …”
Section: Resultsmentioning
confidence: 99%
“…Halogen bonding is being actively studied, and it has been demonstrated that it plays a significant role in biochemistry [22,23], in crystal design and design of functional materials (liquid crystals, molecular receptors, conductors, luminescence emitters, non-linear optical materials, etc.) [24][25][26][27][28][29][30][31][32], in organocatalysis [33][34][35][36][37][38] and in design of pharmaceuticals (here, halogen bonds are considered primarily as a type of hydrophobic functional groups, increasing the lipophilic properties of molecules and allowing them to pass through cell membranes) [39,40]. Besides, the halogen bond has been a subject of numerous theoretical works [41][42][43][44][45][46][47].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, despite the development of excellent proof-ofconcept XB-catalyzed reactions by multiple research groups [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42] , protocols whereby XB catalysis shows clear catalytic advantages in over conventional thiourea catalysis is lacking 21 . Moreover, a conceivable configurational advantage pertaining to XB catalysis would involve the ease of σ-hole tunability via halogen swapping to accommodate challenging substrates-an advantage not well adoptable in thiourea catalysis due to strict requirements of hydrogen atoms for dual HB activation.…”
mentioning
confidence: 99%